Depressed Colorectal Cancer: A New Paradigm in Early Colorectal Cancer. Issue 12 (9th December 2020) - Kudo, Shin-ei; Kouyama, Yuta; Ogawa, Yushi; Ichimasa, Katsuro; Hamada, Tsuyoshi; Kato, Kazuki; Kudo, Koki; Masuda, Takaaki; Otsu, Hajime; Misawa, Masashi; Mori, Yuichi; Kudo, Toyoki; et al.
Abstract : INTRODUCTION: In contrast to most colorectal carcinomas arising from pedunculated or sessile protruded adenomas, submucosal-invasive (pT1) colorectal carcinoma exhibiting a depressed surface (hereinafter, "depressed colorectal carcinoma, " identified by means of high-definition endoscopy) is considered to be derived from depressed precursors. We hypothesized that depressed colorectal neoplasms have unique clinicopathological features different that are different from those of protruded and flat colorectal neoplasms. METHODS: We classified 27, 129 colorectal neoplasms (909 pT1 carcinomas and 26, 220 adenomas) resected between 2001 and 2017 into depressed (211 carcinomas and 109 adenomas), flat (304 carcinomas and 11, 246 adenomas), and protruded subtypes (394 carcinomas and 14, 865 adenomas) and compared their clinicopathological features. As exploratory analyses of pT1 carcinomas, we conducted whole-exome sequencing for 19 depressed and 8 protruded subtypes and RNA sequencing for 8 depressed and 8 protruded subtypes. RESULTS: pT1 carcinomas were more common in depressed lesions (66%) than in protruded (2.6%) and flat lesions (2.6%) ( P < 0.001). Compared with nondepressed pT1 carcinomas, depressed pT1 carcinomas were positively correlated with lymphovascular invasion, tumor budding, and massive submucosal invasion and inversely correlated with the presence of an adenoma component (all P < 0.001). Depressed adenomas were more likely to contain high-grade dysplasia than nondepressed adenomas (49% vs 11%, P < 0.001). A KRAS mutation was observed only in one of the 19 depressed pT1 carcinomas. Relative to protruded carcinomas, depressed carcinomas generally exhibited higher expression of genes related to angiogenesis and epithelial-mesenchymal transition. DISCUSSION: Depressed colorectal neoplasms may harbor a unique combination of malignant histopathological phenotypes and molecular features.